Remarkable Conversion of 2-Thioxo-2,3-dihydroquinazolin-4(1H)-ones into the Corresponding Quinazoline-2,4(1H,3H)-diones: Spectroscopic Analysis and X-Ray Crystallography - Adel S. El-Azab; Nasr Y. Khalil; Alaa A.-M. Abdel-Aziz (Journal of Chemistry)
A simple and efficient new synthetic method to obtain 3-substituted quinazolin-2,4-diones 9–16 by the reaction of 3-substituted 2-thioxo-quinazolin-4-ones 1–8 with sodamide under mild conditions was presented. The structure of the newly synthesized compounds was determined by infrared spectroscopy, UV-visible spectroscopy, nuclear magnetic resonance, and single-crystal X-ray crystallographic analysis. The crystal structure of 6-methyl-3-phenylquinazoline-2,4(1H,3H)-dione (11) [C15H12N2O2: MF = 252.27, triclinic, P-1, a = 7.8495 (13) Å, b = 12.456 (2) Å, c = 13.350 (2) Å, α = 103.322 (3)°, β = 90.002 (3)°, γ = 102.671 (4)°, V = 1237.5 (3) Å3, Z = 4, R = 0.0592, wR = 0.1699, S = 1.039] was determined. In the crystal cell, two identical conformers of compound 11 were found connected by intramolecular hydrogen bonds, responsible for the favourable occurrence of these two independent molecules.